Implementing the environmental dimension of the EU’s Urban Agenda 2014-2020 - Vinci, Ignazio; Cutaia, Fabio (TeMA - Journal of Land Use, Mobility and Environment, 2019)
This work illustrates the planning experience carried out by five municipalities of Western Sicily (Italy) in the the framework of the EU’s urban agenda 2014-2020. The planning process has led to the definition of a Strategy for Sustainable Urban Development (SSUD), whose general objectives are strengthening territorial cohesion and increasing accessibility to local resources. The SSUD action plan, being funded with around 70 millions euro, gives specific importance to sustainable mobility as a mean through which such objectives can be better achieved and reciprocally integrated. After a brief description of the territory targeted by the SSUD (section 1), the paper focuses on the greenway concept within the broader debate on sustainable mobility. In section 3, a series of evidences are provided to identify the demand and potential for the development of sustainable mobility infrastructures in the five cities. In the fourth section, after describing the expceted results of the action plan in the field of sustainable transport, it is argued why in such specific territory a greenway is the best solution to increase accessibility to a broad range of resources and functions (natural sites, landscapes, cultural heritage, urban functions).